Neoadjuvant immunotherapy in mismatch-repair-proficient colon cancers - Pedro B. Tan; Yara L. Verschoor; José G. van den Berg; Sara Balduzzi; Niels F. M. Kok; Marieke E. Ijsselsteijn; Kat Moore; Adham Jurdi; Antony Tin; Paulien Kaptein; Monique E. van Leerdam; John B. A. G. Haanen; et al. (Nature, 2025)
Abstract Immune checkpoint blockade has led to paradigm shifts in the treatment of various tumour types 1–4 , yet limited efficacy has been observed in patients with metastatic mismatch-repair-proficient (pMMR) colorectal cancer 5 . Here we report clinical results and in-depth analysis of patients with early-stage pMMR colon cancer from the phase II NICHE study (ClinicalTrials.gov: NCT03026140). A total of 31 patients received neoadjuvant treatment of nivolumab plus ipilimumab followed by surgery. The response rate was 26% and included six patients with a major pathological response (10% or less residual viable tumour). One patient with an ongoing clinical complete response did not undergo surgery. Circulating tumour DNA was positive in 26 of 31 patients at baseline, and clearance was observed in 5 of 6 responders before surgery, whereas 19 of 20 non-responders remained circulating tumour DNA positive. Responses were observed despite a low tumour mutational burden in all tumours, whereas chromosomal genomic instability scores were significantly higher in responders than in non-responders. Furthermore, responding tumours had significantly higher baseline expression of proliferation signatures and TCF1, and imaging mass cytometry revealed a higher percentage of Ki-67 + cancer and Ki-67 + CD8 + T cells in responders than in non-responders. These results provide a comprehensive analysis of response to neoadjuvant immune checkpoint blockade in early-stage pMMR colon cancers and identify potential biomarkers for patient selection.